Electronic Data Interchange and Demand Forecasting Implications on Supply Chain Management Collaboration: A Customer Service Perspective - Mas'udin, Ilyas; Kamara, Mohammed Sheikh (Jurnal Teknik Industri, 2017)
Customer service is a very important aspect within the supply chain. Through collaboration, the goal of each party within the supply chain is to add value to a product, in order to accelerate good customer service.Â  Good customer service leads to customer satisfaction and most importantly it developed customer loyalty. These are the main goal of ever firm in the supply chain, starting from raw material, production, distribution and down to the final consumer. This work is developed to investigate the impact of supply chain management collaboration activities on customer service in an inter-organizational context. This is done by examining how effective collaboration in supply chain management creating confidence and trust between vendor-customer relationships that provides benefit to both organizations; one of such benefit is improved customer service. This can be obtained through the use of Electronic Data Interchange (EDI), which ensures that products are delivered to customers faster with great accuracy, and demand forecasting and inventory management, which ensures that vendors maintain optimal inventory level so that they always have what customers want in stock. The method used in this work is by gathering information from several articles, journals and text books relating to this research work. There is a total of 49 including journals, books and articles used in this work, all of which are related to this study.